Leveraging YouTube for ELT: A Systematic Review - Nurjannah, Ghina; Mutiasari, Chintia; Tarihoran, Nafan (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
In today's digital era, YouTube is one of the most widely used platforms in teaching English as a foreign language (English Language Teaching / ELT) because it provides authentic and interactive learning content. The increased integration of digital media in the classroom has prompted various studies to explore the effectiveness of YouTube in supporting the language learning process. This study aims to analyze the strategies applied by teachers when using YouTube as an ELT learning medium, the factors that affect its effectiveness, as well as the language skills that are most supported by this platform. The method used is a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. A total of 30 empirical articles were selected from scientific databases such as PubMed, ScienceDirect, Mendeley, and Google Scholar based on specific inclusion and exclusion criteria. The results show that YouTube significantly improves students' speaking and listening skills through exposure to authentic and engaging English-language content. However, internal factors such as student motivation and teacher engagement, as well as external factors such as internet access and material suitability, still affect the overall effectiveness of YouTube use. This study concludes that YouTube is a valuable medium in ELT learning if accompanied by the right strategy and effective mentoring. These findings provide practical implications for educators and researchers to optimize the use of digital media in improving students' language competence.